Can I trust my ears in VR? Literature review of head-related transfer functions and valuation methods with descriptive attributes in virtual reality - Jenny, Claudia; Reuter, Christoph (International Journal of Virtual Reality, 2021)
In this article, we present the current state of the art in binaural audio with the focus on head-related transfer functions (HRTFs) and valuation methods of virtual acoustics with descriptive attributes. This combination provides a methodology, which delivers the basis for research studies in virtual reality (VR) on individual and non-individual head-related transfer functions. Based on the largely explored localization perception of static audio signals, this review offers an overview of the directional hearing during head and sound source movement and multimodality in audiovisual virtual environments. Perceptual quality characteristics provide evaluation methods from which future HRTF VR experiments and virtual environments studies on binaural acoustics could benefit.